SerpinB3/B4 Abates Epithelial Cell-Derived CXCL8/IL-8 Expression in Chronic Rhinosinusitis with Nasal Polyps - Xiangting Bu; Ming Wang; Jing Yuan; Jing Song; Ge Luan; Jiaqi Yu; Yang Wang; Ying Li; Chengshuo Wang; Luo Zhang (Journal of Immunology Research)
Background. Serine proteinase inhibitors, clade B, member 3 (SerpinB3) and B4 are highly similar in amino acid sequences and associated with inflammation regulation. We investigated SerpinB3 and B4 expression and their roles in chronic rhinosinusitis with nasal polyps (CRSwNP). Methods. The expression of SerpinB3 and B4 in nasal mucosa tissues, brush cells, and secretions from CRSwNP patients was measured, and their regulation by inflammatory cytokines were investigated. Their functions were also analyzed using air–liquid interface (ALI)-cultured primary human nasal epithelial cells (HNECs) and transcriptomic analysis. Results. Both SerpinB3 and B4 expression was higher in nasal mucosa, brush cells, and secretions from eosinophilic (E) CRSwNP and nonECRSwNP patients than in healthy controls. Immunofluorescence staining indicated that SerpinB3 and B4 were primarily expressed in epithelial cells and their expression was higher in CRSwNP patients. SerpinB3 and B4 expression was upregulated by interleukin-4 (IL-4), IL-5, IL-6, and IL-17a. Transcriptomic analysis identified differentially expressed genes (DEGs) in response to recombinant SerpinB3 and B4 stimulation. Both the DEGs of SerpinB3 and B4 were associated with disease genes of nasal polyps and inflammation in DisGeNET database. Pathway enrichment indicated that downregulated DEGs of SerpinB3 and B4 were both enriched in cytokine–cytokine receptor interactions, with CXCL8 as the hub gene in the protein–protein interaction networks. Furthermore, CXCL8/IL-8 expression was downregulated by recombinant SerpinB3 and B4 protein in ALI-cultured HNECs, and upregulated when knockdown of SerpinB3/B4. Conclusion. SerpinB3/B4 expression is upregulated in nasal mucosa of CRSwNP patients. SerpinB3/B4 may play an anti-inflammatory role in CRSwNP by inhibiting the expression of epithelial cell-derived CXCL8/IL-8.